Historical-Geographical Features of Tourism Development in Russia - SHULGINA, Daria Pavlovna; SHULGINA, Olga Vladimirovna (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).23, 2019)
The article looks at the main historical periods of tourism development in Russia and the geographical pattern of its expansion across the territory of the country. Historical-geographical features of tourism development in the pre-Revolutionary, Soviet and post-Soviet periods have been identified. Based on archival, literary, statistical and map data sources, the article provides spatiotemporal characteristics of each stage of tourism development in Russia: consumers of travel services and their numbers, main objects of cultural heritage as tourist resources; tourist infrastructure, information support of tourism (published guidebooks, reference books, maps, postcards, and Internet resources).